Initial clinical experience with near-infrared spectroscopy in assessing cerebral tissue oxygen saturation in cerebral vasospasm before and after intra-arterial verapamil injection. (April 2016) - Meng, Lingzhong; Settecase, Fabio; Xiao, Jifang; Yu, Zhaoxia; Flexman, Alana M.; Higashida, Randall T.
Highlights: First study using cerebral tissue oxygen saturation (SctO2 ) assessing the effect of intra-arterial (IA) verapamil injection on vasospasm. Internal carotid artery injection causes differential changes in ipsilateral and contralateral SctO2 . A local vasodilating effect of direct IA verapamil injection is suggested. Recent (days) anterior craniectomy can interfere with SctO2 measurement. The value of cerebral oximetry in this patient population needs further study. Abstract: Cerebral vasospasm is a devastating complication after subarachnoid hemorrhage. The use of cerebral tissue oxygen saturation (SctO2 ) to non-invasively assess changes in cerebral tissue perfusion induced by intra-arterial (IA) verapamil treatment has not been described to our knowledge. A total of 21 consecutive post-craniotomy patients scheduled for possible IA verapamil treatment of cerebral vasospasm were recruited. The effect of IA verapamil injection on SctO2 being continuously monitored on both the left and right forehead was investigated. Comparisons between changes in SctO2 monitored on the ipsilateral and contralateral forehead in relationship to the side of internal carotid artery (ICA) injection were performed. A total of 47 IA verapamil injections (15 left ICA, 18 right ICA, and 14 vertebral artery injections) during 18 neurointerventional procedures in 13 patients were analyzed. IA verapamil administration led to both increases and decreases in SctO2 . Changes in SctO2 ipsilateral to the ICA injection side were more pronounced (p = 0.02 and 0.07 for left and right ICA injections, respectively) and favored compared to contralateral SctO2 changes. We were unable to obtain reliable measurements on the side ipsilateral to the craniotomy during four procedures in three patients, presumably secondary to pneumocephalus. The local cerebral vasodilating effect of IA verapamil injection is suggested by the differential changes in SctO2 ipsilateral and contralateral to the ICA injection side. The inconsistent changes in SctO2 and the limitations of applying cerebral oximetry in this patient population needs to be recognized.